Penguatan Pemahaman Terhadap Sitasi Berbasis Reference Management Software Pada Penulisan Tugas Akhir Skripsi Mahasiswa Fkip Universitas Cenderawasih Tahun 2025 - Rio Wakhid Hujjatul Islam Yasin; Kulyasin (J-Abdimas Cenderawasih, 2026)
Writing a final project or thesis is a vital part of the academic process for students within the Faculty of Teacher Training and Education (FKIP) at Cenderawasih University. One crucial aspect of scientific writing is the ability to organize citations and bibliographies accurately and in accordance with academic standards. However, reality in the field shows that many students still face difficulties in citing correctly, due to both a lack of understanding of scientific citation styles (such as APA, MLA, Chicago, etc.) and limited proficiency in using digital tools like Reference Management Software (e.g., Mendeley or Zotero). Commonly occurring issues include inconsistencies in citation and bibliography formats, errors in listing sources, and even plagiarism practices resulting from a lack of information literacy. Furthermore, many students are not yet familiar with reference management software, which could actually facilitate the citation process automatically and efficiently. To address these issues, this community service activity is designed with a participatory and educational approach through intensive Reference Management Software training. This activity aims to provide a conceptual understanding of the importance of correct citation as well as hands-on technical skills in operating reference management tools. The implementation methods include interactive lectures, direct practice, and individual mentoring and evaluation sessions. Through this activity, it is expected that students will be able to produce higher-quality scientific works, free from plagiarism, and in line with academic standards. The outcomes of this activity include improved participant skills, digital training modules, video tutorials, and the publication of community service scientific articles. This activity also serves as a tangible contribution to fostering a healthy academic culture and supporting the smooth completion of final projects for students at FKIP Cenderawasih University.